Are communities in the United States planning for pedestrians with disabilities? Findings from a systematic evaluation of local government barrier removal plans. (July 2020) - Eisenberg, Yochai; Heider, Amy; Gould, Rob; Jones, Robin
Abstract: Cities with many pedestrian barriers can inhibit community mobility, access to services, and social participation for people with disabilities. Although National Disability Rights policies have been enacted in several nations, it is unclear what progress local governments have made in developing plans and implementing accessibility improvements to the pedestrian infrastructure. The purpose of this study was to evaluate the existence and quality of city plans used to remove barriers for pedestrians with disabilities. We conducted a systematic evaluation of American's with Disabilities Act (ADA) transition plans, for a stratified random sample of local cities and counties. An expert panel developed a quality appraisal tool that we used to evaluate plans. Among the 401 government entities reviewed, only 13% (54) had ADA transition plans readily available. Just seven of the 54 plans we acquired met all the minimum criteria required. Based on those reporting barriers, an average of 65% of curb ramps and 48% of sidewalks were not accessible. Many communities across the US have not developed ADA transition plans for pedestrian infrastructure or have developed low-quality plans. This case study provides insight on local level implementation of barrier removal plans whose lessons may apply inside and outside of the US. Highlights: Pedestrians with disabilities face significant barriers to community mobility. Only a small percentage of communities have developed barrier removal plans. The quality of plans for the pedestrian environment is low. State level pressure & local advocacy can increase inclusive pedestrian planning. Evaluation and monitoring of plan implementation at the local level is needed.